Yahoo Web Search

  1. Sort by

  1. ...e^(-1 * k)] / [e^(-2 * k) (10 / 7) = { [e^(k)]^(-1) } / { [e^(k)]^(-2) } Let e^k = c. I chose c because it's my jam. (10 / 7) = [c^(-1)] / [c...

    2 Answers · Science & Mathematics · 10/06/2015

  2. ...the laws of exponents to get x's exponent in terms of k: ∑ [C(35, k) * (-4x^6)^(35 - k) * (-2/x)^k] (from k=0 to 35) = ∑ [C(35, k) * (-4...

    2 Answers · Science & Mathematics · 27/11/2012

  3. ... for a, b and c, remember k is just a constant... a = 1 b = -k c = k+8 easy enough, now lets solve for x x = (k+- [sqrt(k^2-4(k+8))])/(2...

    4 Answers · Science & Mathematics · 14/10/2010

  4. ...http://en.wikipedia.org/wiki/Binomial_coefficient But since C(n, k) = C(n, n-k), this is also equal to: (a + b)^n = sum over k = 0, n of C...

    1 Answers · Science & Mathematics · 17/10/2010

  5. ... + (-h-k)x + hk            ← b = (-h-k)         ...           c = hk       ...

    1 Answers · Science & Mathematics · 17/09/2011

  6. ..., use the Binomial Probability formula: P(X = k) = C(n, k) * p^k * q^(n-k) n : number of trials 15 k : number...

    1 Answers · Science & Mathematics · 10/05/2017

  7. ...where c is the constant of integration. T(t) = [r*t - r/k + H*β/k + c*exp(-k*t)] Plugging in the values for this problem: r = -2 deg/hr...

    1 Answers · Science & Mathematics · 28/03/2010

  8. ...where c is the constant of integration. T(t) = [r*t - r/k + H*β/k + c*exp(-k*t)] Plugging in the values for this problem: r = -2 deg/hr...

    1 Answers · Science & Mathematics · 29/03/2010

  9. ...a = 11 - 3c, which substituted in the second one gives you k = c(11 - 3c), which as c varies in Z should give you all the possible ...

    2 Answers · Science & Mathematics · 28/02/2010

  10. ...which we could then use the Gamma identity: Gamma(1/2 + k) =√π k! C(2k,k) / 4^k ... to come up with: √π ArcSin[√y] = ∑ (k = 0 to ∞) (1...

    2 Answers · Science & Mathematics · 17/01/2014

  1. Ads
    related to K.C
  1. Try asking your question on Yahoo Answers